African elephants use plant odours to make foraging decisions across multiple spatial scales. (July 2018) - Schmitt, Melissa H.; Shuttleworth, Adam; Ward, David; Shrader, Adrian M.
Abstract : Mammalian herbivores are known to be extremely selective when foraging, but little is known about the mechanisms governing the selection of patches and, at a finer scale, individual plants. Visual examination and direct sampling of the vegetation have previously been suggested, but olfactory cues have seldom been considered. We examined the use of olfactory cues by foraging African elephants, Loxodonta africana, and asked whether they use plant odours to select specific patches or plants when making feeding decisions. Scent-based choice experiments between various preferred and nonpreferred plants were conducted across two spatial scales (between plants and between patches). We used coupled gas chromatography–mass spectrometry (GC–MS) analysis of headspace extracts of volatile organic compounds emitted by the different plant species to explore similarities among the overall odour profiles of each species. We found that elephants selected their preferred plant species across both spatial scales, probably using differences in plant odour profiles. The ability to differentiate between plant odours allowed elephants to reduce their search time by targeting preferred plant species both within a feeding station and between patches. This suggests that olfactory cues probably play an important role in driving herbivore foraging decisions across multiple spatial scales. Highlights: Plants emit odours that can reflect their chemical properties and identities. The use of plant odour in mammalian herbivore foraging decisions is not well known. Our study suggests that African elephants use plant odours to make diet choices. These decisions span across two spatial scales.